MANGANESE(III) BINDING TO A PYOVERDINE SIDEROPHORE PRODUCED BY A MANGANESE(II)-OXIDIZING BACTERIUM - Parker D.L.; Sposito G.; Tebo B.M. (My University, 2004)
The possible roles of siderophores (high affinity chelators of iron(III)) in the biogeochemistry of manganese remain unknown. Here we investigate the interaction of Mn(III) with a pyoverdine-type siderophore (PVDMnB1) produced by the model Mn(II)-oxidizing bacterium Pseudomonas putida strain MnB1. PVDMnB1 confirmed typical pyoverdine behavior with respect to: (a) its absorption spectrum at 350–600 nm, both in the absence and presence of Fe(III), (b) the quenching of its fluorescence by Fe(III), (c) the formation of a 1:1 complex with Fe(III), and (d) the thermodynamic stability constant of its Fe(III) complex. The Mn(III) complex of PVDMnB1 had a 1:1 Mn:pvd molar ratio, showed fluorescence quenching, and exhibited a light absorption spectrum (Amax = 408–410 nm) different from that of either PVDMnB1-Fe(III) or uncomplexed PVDMnB1. Mn(III) competed strongly with Fe(III) for binding by PVDMnB1 in culture filtrates (pH 8, 4°C). Equilibration with citrate, a metal-binding ligand, did not detectably release Mn from its PVDMnB1 complex at a citrate/PVDMnB1 molar ratio of 830 (pH 8, 4°C), whereas pyrophosphate under the same conditions removed 55% of the Mn from its PVDMnB1 complex. Most of the PVDMnB1-complexed Mn was released by reaction with ascorbate, a reducing agent, or with EDTA, a ligand that is also oxidized by Mn(III). Data on the competition for binding to PVDMnB1 by Fe(III) vs. Mn(III) were used to determine a thermodynamic stability constant (nominally at 4°C) for the neutral species MnHPVDMnB1 (log K = 47.5 ± 0.5, infinite dilution reference state). This value was larger than that determined for FeHPVDMnB1 (log K = 44.6 ± 0.5). This result has important implications for the metabolism, solubility, speciation, and redox cycling of manganese, as well as for the biologic uptake of iron.